A molecular guide to systemic therapy in salivary gland carcinoma. Issue 5 (1st March 2023) - Weaver, Alice N.; Lakritz, Stephanie; Mandair, Divneet; Ulanja, Mark B.; Bowles, Daniel W.
Abstract: Salivary gland carcinomas (SGC) are a rare and variable group of head and neck cancers with historically poor response to cytotoxic chemotherapy and immunotherapy in the recurrent, advanced, and metastatic settings. In the last decade, a number of targetable molecular alterations have been identified in SGCs including HER2 upregulation, androgen receptor overexpression, Notch receptor activation, NTRK gene fusions, and RET alterations which have dramatically improved treatment outcomes in this disease. Here, we review the landscape of precision therapy in SGC including current options for systemic management, ongoing clinical trials, and promising future directions.